Pengaruh Pembelajaran Berdiferensiasi dengan Model Project Based Learning dalam Merancang Pembangkit Tenaga Listrik Melalui Canva terhadap Kemampuan Berpikir Kreatif dan Literasi Digital Siswa Sekolah Dasar - Arif Zulkifli (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The main competencies in modern education are the 4C skills, which consist of critical thinking, creativity, collaboration, and communication, and are highly needed by the current generation. However, the results of the 2022 international student assessment (PISA) show that Indonesian students' creative thinking skills are ranked low, and according to a national survey by BPS in 2024, students' digital literacy in learning is still very lacking. Therefore, this study aims to examine the implementation of differentiated PjBL learning to develop students' creative thinking and digital literacy skills in elementary school students. This research was conducted experimentally using the "Pre-test Post-test Control Design" at SD Negeri Ditotrunan 01, Lumajang District, Lumajang Regency. As the experimental class, class 4A implemented differentiated PjBL learning with a project designing a power plant using Canva, and as the control class, class 4B used the same material but with conventional learning as usual. The measurement of students' creative thinking abilities was conducted through pre-tests and posttests, including indicators of creative thinking abilities such as fluency, flexibility, originality, and elaboration. Meanwhile, the measurement of students' digital literacy was conducted through initial and final observations, which included digital literacy indicators such as searching on the internet, hypertextual navigation, content evaluation, and knowledge assembly. The analysis method used was Kruskal Wallis because the obtained data did not follow a normal distribution. The analysis results prove that the average post-test scores of the experimental class were higher than those of the control class on all indicators of students' creative thinking and digital literacy abilities, with a significant difference (p < 0.05). In conclusion, differentiated PjBL learning significantly affects students' creative thinking and digital literacy skills in designing power plants using Canva among elementary school students.
Entry oleh Arif 2026 Maret 16
Keywords: Differentiated Learning; PJBL Model; Canva Media; Creative Thinking Skills; Students' Digital Literacy